Clinical Outcomes During Admissions for Heart Failure Among Adults With Congenital Heart Disease. Issue 16 (20th August 2019) - Agarwal, Anushree; Dudley, Carson W.; Nah, Gregory; Hayward, Robert; Tseng, Zian H.
Abstract : Background: Heart failure (HF) admissions in adults with congenital heart disease (CHD) are becoming more common. We compared in‐hospital and readmission events among adults with and without CHD admitted for HF. Methods and Results: We identified all admissions with the primary diagnosis of HF among adults in the California State Inpatient Database between January 1, 2005 and January 1, 2012. International Classification of Disease (ICD) codes identified the type of CHD lesion, comorbidities, and in‐hospital and 30‐day readmissions events. Adjusted odds ratio (AOR, 95% CI) was calculated after adjusting for admission year, age, sex, race, household income, primary payor, and Charlson comorbidity index. Of 203 759 patients admitted for HF, 539 had CHD other than atrial septal defect. Compared with patients admitted for HF without CHD, those with CHD were younger, more often male, and had fewer comorbidities as determined by Charlson comorbidity index. On multivariate analysis, CHD patients admitted for HF had higher odds of length of stay ≥7 days (AOR 2.5 [95% CI 2.0–3.1]), incident arrhythmias (AOR 2.8 [95% CI 1.7–4.5]), and in‐hospital mortality (AOR 1.9 [95% CI 1.1–3.1]). Also, CHD patients had lower odds of readmission for HF (AOR 0.6 [95% CI 0.3–0.9]), but similar odds of other 30‐day readmission events. Complex CHD patients had higher odds of length of stay ≥7 days (AOR 1.9 [95% CI 1.1–3.3]) than patients with noncomplex CHD lesions, but similar odds of all other clinical outcomes. Conclusions: Among patients admitted with the primary diagnosis of HF in California, adults with CHD have substantially higher odds of longer length of stay, incident arrhythmias, and in‐hospital mortality compared with non‐CHD patients. These results suggest a need for HF risk stratification strategies and management protocols specific for patients with CHD.